Influence of the physicochemical parameters of solvents in the extraction of bioactive compounds from Parinari macrophylla Sabine (Chrysobalanaceae) - Balde, Mamadou; Ennahar, Said; Dal, Stephanie; Sigrist, Severine; Wele, Alassane; Marchioni, Eric; Julien-David, Diane (European Journal of Chemistry, 2018)
The extraction of bioactive compounds from medicinal plants requires methods which are as diverse as the chemical nature of the compounds themselves. In this study, a 96-well microplate was used where solvent mixtures spanning wide ranges of selectivity and polarity were tested with the objective of extracting a broad range bioactive compounds from plant material. Microplate wells were filled with plant material and the solvents and their mixtures were added. The obtained extracts were assessed in terms of their total antioxidant activity, oxygen radical absorbance capacity and effects on cell viability. An aqueous extract, generally used by traditional therapists, was also included in the study. The results showed that the extracts using methanol with acetic acid (0.1%, v:v), chloroform/ethanol, butanol/DMF, butanol/acetonitrile, ethylene glycol with acetic acid (0.1%, v:v), MTBE/DMSO, ethylene glycol, pentane/ethanol (v:v), ethanol, DMF, DMF with acetic acid (0.1%, v:v), DMSO, DMSO with acetic acid (0.1%, v:v) and THF had a higher antioxidant activity than the aqueous extract. Extracts with greater antioxidant activity than the aqueous extract were obtained largely from solvent mixtures with the exception of ethanol, DMF, DMSO and THF. The antioxidant activity obtained in TEAC varied between 1474.1±4.4 and 3183.0±16.0 μmol TE/g dry extract respectively for aqueous and THF extracts; in ORAC between 1727.7±8.4 and 2683.5±11.7 μmol TE/g dry extract for aqueous and DMSO acetic acid 1%, respectively, with mean ±SEM. In TEAC the THF extract had the highest antioxidant potential with 3183.0±16.0 μmol TE / g dry extract. The DMSO acetic acid (0.1%, v:v) extract had the highest antioxidant potential in ORAC with 2683.5±11.7 μmol TE / g dry extract. Cell viability test using β-pancreatic cells showed that only the acidified methanol extract was toxic after one hour of incubation. After 24 hours, cell viability was less than 70% for extracts using butanol/acetonitrile, MTBE/DMF, acidified methanol, pentane/ethanol and acidified DMF.